Diffuse dermal angiomatosis: a rare cause of painful ulceration in renal insufficiency. (1st June 2022) - Matos, Ana Luísa; Nogueira, Rui; Flor, Duarte; Alves, Francisca; Cardoso, José Carlos; Vieira, Ricardo
Abstract: Diffuse dermal angiomatosis is a rare, benign, reactive cutaneous vascular proliferation that has been reported in the context of end‐stage renal failure and can rarely be associated with arteriovenous fistulas. We report a striking clinical resolution following prompt diagnosis and subsequent arteriovenous fistula reversal. This case further demonstrates that accurate diagnosis is particularly rewarding since correct therapeutic approach can be curative.